Level of Preparedness for COVID-19 and Its Associated Factors among Frontline Healthcare Providers in South Gondar Public Hospitals, Northwest Ethiopia, 2020: A Multicenter Cross-Sectional Study. (2nd March 2021) - Chanie, Ermias Sisay; Feleke, Dejen Getaneh; Fetene, Sheganew; Tigabu, Agimasie; Asnakew, Sintayehu; Tiruneh, Tegenaw; Mekie, Maru; Ayehu, Gashaw Walle; Bayih, Wubet Alebachew
Abstract : Introduction . Although the efforts at global and national levels have attempted to decrease the COVID-19 pandemic, the low level of preparedness among healthcare providers is a challenge mainly in developing countries. Hence, this study is aimed at assessing the level of preparedness for COVID-19 and its associated factors among frontline healthcare providers in South Gondar public hospitals, northwest Ethiopia. Methods and Materials . A hospital-based cross-sectional study was conducted among 207 selected healthcare providers who were working in South Gondar public hospital from July 08 to August 29, 2020. A pretested structured questionnaire was used to collect data. The healthcare providers were selected through simple random sampling techniques. Both bivariable and multivariable logistic regressions with a 95% confidence interval were fitted with 95% CI to establish the associated factors with a low level of preparedness. A p value < 0.05 was considered statistically significant. Results . The overall level of preparedness among healthcare providers for COVID-19 was found to be 41.3% (95% CI: 37.4, 44.7). Only 81 (40.1%) healthcare providers had prepared for telling their family and friends if they are infected with COVID-19. Besides, only 23.8% of healthcare providers obtained alcohol-based hand sanitizer in every patient room. Factors associated with a low level of preparedness include being male (AOR = 2.5, 95% CI: 1.22–4.94), unmarried (AOR = 3.4, 95% CI: 1.44–8.00), and working experience less than five years (AOR = 3.4, 95% CI: 1.29-9.09). Conclusion . The level of preparedness among frontline healthcare providers towards COVID-19 was found to be very low. In the future, more emphasis should be placed on healthcare providers who are male, unmarried, and had working experience of lower than five years to decrease the burden of the COVID-19 pandemic.